2013
DOI: 10.1111/1365-2664.12107
|View full text |Cite
|
Sign up to set email alerts
|

Does it make economic sense to restore rivers for their ecosystem services?

Abstract: Summary1. Temperate forests managed to maximize sustainable yield of wood products can reduce the availability of dead wood on the forest floor and in adjacent streams, which in turn can impair ecological processes such as retention and transformation of organic matter. Lack of tools to link ecological processes with their effects on human well-being leads forest managers to ignore the cost on other services from terrestrial and aquatic ecosystems. 2. We examine how adding dead wood to restore stream channel c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(59 citation statements)
references
References 37 publications
(47 reference statements)
2
53
0
Order By: Relevance
“…Perceived changes in fish provisioning seemed to influence the overall perceptions of restoration benefits (Acuña et al 2013). Abundance of the target fish species may be an indicator of ecological integrity, but it is also seen as a resource that affects fisheries opportunities, the attractiveness of the river, and local employment (Dufour andPiégay 2009, Schultz et al 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Perceived changes in fish provisioning seemed to influence the overall perceptions of restoration benefits (Acuña et al 2013). Abundance of the target fish species may be an indicator of ecological integrity, but it is also seen as a resource that affects fisheries opportunities, the attractiveness of the river, and local employment (Dufour andPiégay 2009, Schultz et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Palmer et al (2005) have suggested that ecological, stakeholder, and learning success form the main cornerstones for effective river restoration. Despite increasing interest, ecosystem services and other socioeconomic outcomes have rarely been identified in this context, limiting our understanding of the full benefits and costs of ecological restoration (Acuña et al 2013, Wortley et al 2013.…”
Section: Introductionmentioning
confidence: 99%
“…Coarser sediment elements in more structurally intact river reaches indicate that erosion and subsequent fine sediment deposition may contribute additional fine sediments in many of the more disturbed reaches of the studied river (Nascimento et al, 2012). Accordingly, additional structural elements, such as coarse particulate organic matter, may be especially important for the biotic community and should be a focus of habitat restoration in human-impacted tropical rivers (Acuña et al, 2013). Conversely, massive gravel extraction in the few river reaches exhibiting coarser sediments should be especially deleterious.…”
Section: Granulometrymentioning
confidence: 98%
“…areas that can be seen up to 65 times from viewpoints). This map was classified in a qualitative scale map using the natural breaks categories of the visibility raster map ranging from: very low (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12), low (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25), medium (26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37), high (38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)…”
Section: Wine Productionmentioning
confidence: 99%
“…Subject to (2) Where is a control variable indicating if a planning unit (i = 1,…, N) is selected = 1) or not = 0) and is the cost of the planning unit. Eq.…”
Section: Spatial Prioritizationmentioning
confidence: 99%